2018
DOI: 10.1159/000493714
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein Inhibits Proliferation Activity of Human Colorectal Cancer Cells HCT116 Through Downregulation of Ezrin

Abstract: Background/Aims: The present study was aimed at examining Ezrin expression in human colorectal cancer (CRC) tissues and elucidating the influence of baicalein on the proliferation of HCT116 cells. Methods: The expression of Ezrin was determined by qRT-PCR and immunohistochemistry. HCT116 cells were divided into four groups- baicalein groups with various concentrations, pcDNA3.1-Ezrin group, si-Ezrin group and dual inhibitory group (baicalein + si-Ezrin). CCK-8 assay and flow cytometry (FCM) were employed to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…Baicalein is a major bioactive flavone derived from the dry roots of S. baicalensis . It has been shown that treatment with baicalein inhibits cell proliferation and enhances apoptosis and autophagy of many types of cancer, including HCC [29], bladder cancer [30], and colorectal cancer [31]. Previously, studies have also demonstrated that baicalein exerts multiple effects against HCC, mainly involving the inhibition of cell proliferation by arresting the cell cycle, suppression of metastasis, induction of apoptosis, as well as induction of autophagy via the modulation of associated molecules and signaling pathways [32].…”
Section: Discussionmentioning
confidence: 99%
“…Baicalein is a major bioactive flavone derived from the dry roots of S. baicalensis . It has been shown that treatment with baicalein inhibits cell proliferation and enhances apoptosis and autophagy of many types of cancer, including HCC [29], bladder cancer [30], and colorectal cancer [31]. Previously, studies have also demonstrated that baicalein exerts multiple effects against HCC, mainly involving the inhibition of cell proliferation by arresting the cell cycle, suppression of metastasis, induction of apoptosis, as well as induction of autophagy via the modulation of associated molecules and signaling pathways [32].…”
Section: Discussionmentioning
confidence: 99%
“…Baicalein , 5,6,7-Trihydroxyflavone, isolated from Scutellaria baicalensis and Scutellaria lateriflora (71), holds potential in treating breast cancer (72), colorectal cancer (73), bladder cancer (74), etc. Baicalein may reverse ABCB1 mediated MDR as shown on ABCB1 gene transfected Madin-Darby canine kidney II (MDCK II) cells (75).…”
Section: Multi-functional Flavonoids Overcome Mdr In Cancermentioning
confidence: 99%
“…Baicalein is known as an effective inhibitor in the tumor progression. For instance, Chen et al reported that baicalein blocked cell proliferative activity and cell cycle in colorectal cancer; 23 Yang et al declared that cell viability in bladder cancer was impeded while apoptosis was induced by baicalein; 24 Ma et al found that baicalein treatment resulted in cell proliferation inhibition and cell cycle arrest of prostate…”
Section: Discussionmentioning
confidence: 99%